AC Drive Traction System of High-power HXN5 Diesel Locomotive - 陈智豪; 张义; 杨格; 何良 (Kongzhi Yu Xinxi Jishu)
This paper introduces the composition, technical characteristics, performance parameters and cooling system of AC drive traction system for high-power HXN5 diesel locomotive, focusing on the working principle and function features of core components in electric drive system.